PENGARUH PAJAK, MEKANISME BONUS, UKURAN PERUSAHAAN, DAN TUNNELING INCENTIVE TERHADAP PELAKSANAAN TRANSFER PRICING - Maharani, Brigita Aprilia Dessy; Budiantara, Martinus (STIE DWI SAKTI BATURAJA, 2024)
This study examines the effect of taxes, bonus mechanisms, tunneling incentives, and company size on transfer pricing decisions. This study uses secondary data using purposive sampling method. 30 non-financial companies listed on the Indonesia Stock Exchange in 2019-2022 were taken as samples in this study. The data analysis method used in this study is logistic regression through the SPSS 22 program for windows. The results of this study indicate that taxes, bonus mechanisms, tunneling incentives and company size have no significant effect on transfer pricing decisions.